Appraising income securitisation in the public sector: the sale of student rents at Keele University. (20th May 2009) - Armstrong, Peter
Already a mainstream source of finance in the private sector, the exchange of future income for present cash is increasingly being promoted by the international financial services industry as a means of funding capital projects in the public sector. This paper reports on the value-for-money aspects of one such scheme: the securitisation of the rents on its student accommodation by a small UK university. The case strongly suggests that there are lessons to be learnt on the appraisal of such schemes and on their accounting treatment. Inter alia, the paper also comments on the adequacy of financial management at the level of institutions of higher education and on the oversight provided by the Higher Education Funding Council for England and, at one remove, by the National Audit Office.